Quantifying the Impact of the Dust Torque on the Migration of Low-mass Planets. II: the Role of Pebble Accretion in Planet Growth within a Global Planet Formation Model - Guilera, Octavio Miguel (2025)
Although dust constitutes only about 1% of the mass in a protoplanetary disk, recent studies reveal its substantial impact on the torques experienced by low- and intermediate-mass planetary cores. In this study, we present the first comprehensive analysis of the dust torque’s influence on the evolution of growing planetary embryos as they migrate through a protoplanetary disk and undergo gas and pebble accretion. Our global model incorporates viscous accretion and X-ray photoevaporation effects on the gaseous disk while also accounting for the dynamic processes of dust growth and evolution, including coagulation, drift, and fragmentation. Our >fidings demonstrate that dust torque significantly affects planetary migration patterns, particularly facilitating prominent outward migration for planets forming within the water-ice line. This outward thrust arises from an enhanced dust-to-gas mass ratio in the inner disk, driven by the inward drift of pebbles from the outer regions. Conversely, for planets that originate beyond the water-ice line, while the dust torque attenuates inward migration, it does not substantially alter their overall migration trajectories. This is attributed to the rapid reduction in dust-to-gas mass ratio, resulting from swift pebble drift and the short formation timescales prevalent in that region. Overall, our findings highlight the critical role of dust torque in shaping the migration of low- and intermediate-mass planets, particularly in conditions where increased dust concentrations amplify its effects. These insights have significant implications for understanding the formation timescales, mass distributions, and compositional characteristics of emerging planetary systems.